Riscando o asfalto: disputa, participação e aprendizagem no rolimã - Luciano Silveira Coelho (2022)
The aim of this study was to understand who are the subjects, places and learning concerning the trolley events in the Metropolitan Region of Belo Horizonte (RMBH). This research was conceived from the conceptual and methodological principles of ethnography, which value a dense and long-lived fieldwork, a continuous and necessary exercise of alterity, an openness to new research techniques and instruments and also a willingness to go beyond the observation and transform their own field experiences into scientific data. Therefore, it was extremely important for me to appropriate these concepts, to be inspired by other ethnographies and, from there, to build strategies and make the most appropriate choices in the context of the events of the trolley car. The fieldwork was developed mainly in the “meetings” of Praça do Papa, in Buritis neighborhood and in Esplanade of Mineirão Stadium. However, to learn more about the events and initiatives related to trolley in the RMBH, it was also necessary to know other places where events characterized as "rolês", "corujões" and "gp's" took place. At different times and with different frequencies, there were 46 field trips, from September 2019 to June 2022, in events that lasted between two and three hours. The first impressions indicated that the trolley movement in the RMBH was a broad, cohesive and coordinated action of a group of people around the same purpose. With a prolonged stay in the field, I found a movement marked by disputes, interests and multiple appropriations that limit, while shaping, a community of practice (LAVE and WENGER, 1991). In this scenario, men and women, adults and children, apprentices and veterans, participate, constitute and are constituted (LAVE, 2019) by a polysemic, contradictory and invariably situated practice. For this reason, “playing”, “ride” or “pilot” a trolley are skills that are not established by an accumulation of mental representations that are converted into body movements, but by a perceptive agency, through a process of education of attention (INGOLD, 2000). Without pretending to forge conclusive and totalizing analyses, the present study adds to a broad and contemporary field of research that has been building more accurate understandings about the different ways of being children in urban contexts.